Thermal Behavior of Agricultural Waste in Microwave-assisted Pyrolysis: A Focus on Temperature Parameters - Caroko, Novi; Syamsiro, Mochamad; Wahyudi, Wahyudi; Fajrin, Qorina Vivianty (Universitas Muhammadiyah Yogyakarta, 2025)
Temperature is a crucial parameter in microwave-assisted pyrolysis, as it serves as a basis for evaluating the thermal treatment of a material. This study aims to assess temperature-related parameters and identify the optimal mixture composition for the microwave-assisted pyrolysis of agricultural waste, specifically corn cob, groundnut shell, and rice husk, combined with charcoal. The research employed thermogravimetric analysis (TGA), with agricultural waste mixed with a microwave absorber in the form of charcoal at various composition ratios: 100:0, 75:25, 50:50, 25:75, and 0:100. The results indicate that the composition of feedstock significantly affects temperature parameters. The addition of charcoal was found to increase the maximum temperature and heating rate while simultaneously reducing energy consumption. For all tested agricultural waste, higher charcoal compositions at ratios of 75:25, 50:50, and 25:75 resulted in substantial improvements. Maximum temperature increased by up to 230%, heating rate by up to 497.90%, and energy consumption decreased by up to 80.45% compared to pure agricultural waste biomass. This indicates that 75:25 mixtures of corn cobs, groundnuts, and rice husks with charcoal can be recommended for the pyrolysis process, as they are capable of reaching the pyrolysis temperature range of approximately 400°C–800°C.